2005
DOI: 10.1074/jbc.m505974200
|View full text |Cite
|
Sign up to set email alerts
|

Why Is Quinidine an Inhibitor of Cytochrome P450 2D6?

Abstract: had only a minor effect on the inhibition of bufuralol 1-hydroxylation and dextromethorphan O-demethylation and on binding. In contrast to the wild-type enzyme, a number of the mutants studied were found to be able to metabolize quinidine. E216F produced O-demethylated quinidine, and F120A and E216Q/D301Q produced both O-demethylated quinidine and 3-hydroxyquinidine metabolites. Homology modeling and molecular docking were used to predict the modes of quinidine binding to the wild-type and mutant enzymes; thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Keizers et al (73) found that the same mutant abolished the O-demethylation of 7-methoxy-4-(aminomethyl)-coumarin, whereas bufuralol metabolism was unaffected. Very recently, McLaughlin et al (74) reported that the F120A mutation changed the role of quinidine from being a potent inhibitor to becoming a substrate. The position of Phe-120 in the crystal structure is in clear agreement with these studies.…”
Section: Resultsmentioning
confidence: 99%
“…Keizers et al (73) found that the same mutant abolished the O-demethylation of 7-methoxy-4-(aminomethyl)-coumarin, whereas bufuralol metabolism was unaffected. Very recently, McLaughlin et al (74) reported that the F120A mutation changed the role of quinidine from being a potent inhibitor to becoming a substrate. The position of Phe-120 in the crystal structure is in clear agreement with these studies.…”
Section: Resultsmentioning
confidence: 99%
“…In particular the hydroxyl group of quinidine (rather than the basic nitrogen atom, known to be relevant for the interactions with CYP2D6) forms the dominant interaction with Glu216 [16].…”
Section: Model Building and Structural Analysismentioning
confidence: 99%
“…The cavity entrance is bordered by a number of long charged/hydrophilic side chains from the F helix (Gln210, Glu211, Lys214, and Arg221) and residues from the region between the two strands of ␤ sheet 4 (side chains of Ala482 and Ser486 and main chain atoms of Val485), with the side chains of Asp179 (helix E) and Thr312 (helix I) also in the vicinity [15]. Among the residues of the cavity, Phe120, Glu216, Asp301, and Met374, in particular are considered to be the most relevant for the inhibitor and substrate binding [16].…”
Section: Model Building and Structural Analysismentioning
confidence: 99%
“…However, only 39% of the amount of NADPH consumed was found to serve in product formation, the remainder being utilized in the formation of H 2 O 2 and water [146]. Tight binding of the inhibitor quinidine, generating a mixture of low-and high-spin CYP2D6 [145][146][147], gave origin to a cyclic voltammetric profile aberrant from that observed with prototypic substrates [141]. Docking might be influential on the release of extra water in incubations with reconstituted hemoprotein, though there is no evidence for biotransformation of the nitrogenous base [146].…”
Section: The Cyp2d Enzymesmentioning
confidence: 99%